Attachment Styles and Intolerance of Uncertainty as Predictors of Generalized Anxiety in Adults - Binaz Bozkur; Özlem Eryılmaz; Mustafa Güler (Uluslararası Türk Eğitim Bilimleri Dergisi)
This study aims to examine the relationship between intolerance of uncertainty and attachment styles and generalized anxiety and the predictive status of these variables for generalized anxiety. The research study group consists of 938 people (634 women, 304 men) over the age of 18. In the data analysis, the relationship of the variables with each other was examined with the Pearson Correlation Coefficient; predictive status was examined by Stepwise Multiple Linear Regression Analysis. The results of the correlation analysis revealed that there is a positive correlation between generalized anxiety, intolerance of uncertainty, and insecure attachment styles (anxious and avoidant attachment) and a negative correlation with secure attachment style. The predictive analysis results show that both intolerance of uncertainty and attachment styles are significant predictors of generalized anxiety disorder. These data obtained from a large study group reveal that intolerance of uncertainty and attachment styles are important variables associated with generalized anxiety disorder.